Recent advances on research into interventions to improve food safety in Africa - Grace, Delia (International Livestock Research Institute, 2025)
Africa bears the highest per capita burden of foodborne disease globally, and much of this is the result of consumption of fresh foods sold in traditional or informal markets. These include open public markets, small shops, kiosks or dukas, street food and food sold in pubs and eateries. Recent evidence suggests the informal sector is likely to persist for years if not decades.